2013
DOI: 10.1155/2013/429393
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Action of Conjugated Linoleic Acid on Human MCF-7 Breast Cancer Cells Mediated by Enhancement of Gap Junctional Intercellular Communication through Inactivation of NF-κB

Abstract: The major conjugated linoleic acid (CLA) isomers, c9,t11-CLA and t10,c12-CLA, have anticancer effects; however, the exact mechanisms underlying these effects are unknown. Evidence suggests that reversal of reduced gap junctional intercellular communication (GJIC) in cancer cells inhibits cell growth and induces cell death. Hence, we determined that CLA isomers enhance GJIC in human MCF-7 breast cancer cells and investigated the underlying molecular mechanisms. The CLA isomers significantly enhanced GJIC of MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…This correlation is a possible reason for the influence of chemotherapeutics which focus on ErbB receptors as their main target but also manipulate gap junctions in conventional breast tumor cells and in tumor stem cells [ 151 , 152 , 153 ]. In particular, it could be shown that the apoptosis activity level of conjugated linoleic acid via stimulation of caspase-3 in MCF-7 breast cancer cells is dependent on gap junction permeability [ 154 ]. Modulators of gap junction permeability derive from pesticides and polychlorinated aromatic compounds, but hormones like estradiol can also induce carcinogenesis in breast epithelial cells with increased ErbB receptor number [ 155 , 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is a possible reason for the influence of chemotherapeutics which focus on ErbB receptors as their main target but also manipulate gap junctions in conventional breast tumor cells and in tumor stem cells [ 151 , 152 , 153 ]. In particular, it could be shown that the apoptosis activity level of conjugated linoleic acid via stimulation of caspase-3 in MCF-7 breast cancer cells is dependent on gap junction permeability [ 154 ]. Modulators of gap junction permeability derive from pesticides and polychlorinated aromatic compounds, but hormones like estradiol can also induce carcinogenesis in breast epithelial cells with increased ErbB receptor number [ 155 , 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although 24 h treatment with 5−40 μM c9t11-CLA did not affect viability of MCF-7 cells in one study, 31 MCF-7 cell viability was reduced by a 24 h treatment with 40 μM c9t11-CLA and t10c12-CLA in another study. 32 In a further study, both c9t11-CLA and t10c12-CLA decreased MCF-7 cell viability through apoptosis at a concentration of 50 μM.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…To enhance the antitumor activity, we determined whether suicide gene system combined with ATRA could potentiate the destruction of breast cancer. Three connexin proteins have been identified in breast tissues, including Cx43, Cx26 and Cx32 (9). Expression of Cx26 and Cx32 are enhanced during pregnancy and further increased during lactation in normal breast tissues (10).…”
Section: Discussionmentioning
confidence: 99%
“…Three connexins (Cx43, Cx26 and Cx32) have been shown to be expressed in the human breast tissue in different temporal and spatial patterns. In normal human breast tissues, Cx26 and Cx32 are present in the mammary epithelium, whereas Cx43 is localized mainly to myoepithelial cells (9,10). It was reported that Cxs are often reduced or lost resulting in significantly decreased GJIC in tumor tissues, thus decreased gap junctional communication may be involved in oncogenesis (11).…”
Section: Introductionmentioning
confidence: 99%